2020
DOI: 10.1101/2020.06.29.178020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active integrins regulate white adipose tissue insulin sensitivity and brown fat thermogenesis

Abstract: AbstractReorganization of the extracellular matrix is a prerequisite for healthy adipose tissue expansion, whereas fibrosis is a key feature of adipose dysfunction and inflammation. However, very little is known about the direct effects of impaired cell-matrix interaction in adipocyte function and insulin sensitivity. Using adipose selective deletion of β1 integrin (Itgb1adipo-cre) and Kindlin-2 (Kind2adipo-cre), we demonstrate here tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In accordance with the results, previous studies have shown that defects in lipogenesis-related factors, including ACC, SCD, ACLY, DGAT1/2 and BSCL2, lead to loss of adipose tissue and are associated with systemic metabolic abnormalities (44)(45)(46)(47)(48)(49)(50)(51). Similar phenotypes were found with defects of the extracellular matrix and related signaling molecules, including collagen, FBN, integrin, and FAK (52)(53)(54)(55)(56)(57).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 88%
“…In accordance with the results, previous studies have shown that defects in lipogenesis-related factors, including ACC, SCD, ACLY, DGAT1/2 and BSCL2, lead to loss of adipose tissue and are associated with systemic metabolic abnormalities (44)(45)(46)(47)(48)(49)(50)(51). Similar phenotypes were found with defects of the extracellular matrix and related signaling molecules, including collagen, FBN, integrin, and FAK (52)(53)(54)(55)(56)(57).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 88%
“…Thus, taken together, it is evident that it is the insulin resistnce in adipose tissue that leads to inflammation and not inflammation itself that leads to adipose tissue insulin resistance. In line with these findings, Ruiz-Ojeda et al [59] demonstrated that isolated adipocytes from subcutaneous WAT of adipose-specific knockout of Kindlin-2, an integrin activator, showed local insulin resistance read by reduced Akt phosphorylation and decreased glucose uptake. However, no differences were observed in the proinflammatory markers in the adipose tissue of chow diet-fed mice [59].…”
Section: Ecm Remodeling Insulin Signaling and Glucose Homeostasismentioning
confidence: 76%
“…In line with these findings, Ruiz-Ojeda et al [59] demonstrated that isolated adipocytes from subcutaneous WAT of adipose-specific knockout of Kindlin-2, an integrin activator, showed local insulin resistance read by reduced Akt phosphorylation and decreased glucose uptake. However, no differences were observed in the proinflammatory markers in the adipose tissue of chow diet-fed mice [59].…”
Section: Ecm Remodeling Insulin Signaling and Glucose Homeostasismentioning
confidence: 76%
See 2 more Smart Citations